Parenting style as a predictor of music preference - Warrener, E.; Krause, A.; North, Adrian (Sage Publications Ltd., 2018)
Although previous research has established relationships between perceived parenting styles and children’s deviant behaviours and links between these behaviours and a liking for intense and rebellious music, no research has explored the associations between perceived parenting styles and children’s liking for different music styles. Whereas previous research has considered musical taste by looking at a small number of individual difference variables in isolation from one another, the present research used a cross-sectional correlational design to investigate whether parenting styles, the Big Five personality traits, sensation seeking, age, and gender were associated with a liking for different music styles. In total, 336 Australians completed an online, self-report questionnaire. Analyses demonstrated there were relationships between five of the six parenting style variables and five of the music styles considered. This indicates that various parenting styles were associated with musical taste, and the nature of these associations extends well beyond those concerning rebellious music and neglectful parenting that have been identified by previous research.